PENERAPAN PEMBELAJARAN KOOPERATIF TEAM ACCELERATED INSTRUCTION (TAI) UNTUK MENINGKATKAN MOTIVASI DAN HASIL BELAJAR SISWA - Mutia Mutia (Universitas Islam Negeri (UIN) Mataram, 2016)
This research aims to determine how to implement Team Accelerated Instruction (TAI) of cooperative learning model to increase student motivation and student learning outcomes. The current research is a classroom action research with three cycles, each cycle consisting of four phases: planning, action, observation, and reflection. The research was conducted in mathematic course for class VIII-3 SMPN 14 Bengkulu with 37 students consisting of 17 boys and 20 female. From the analysis of student questionnaire, the motivation level of students from the first cycle to the third cycle has increased. In the first cycle, students a positive attitude towards learning TAI to improve student motivation is equal to 78.38%, on the second cycle increased to 83.78%, and the third cycle increased to 94.59%. This increase was followed by student activity. Observations indicate activity of students in the first cycle is at less criteria with an average score of 15, the second cycle increased in sufficient criteria with an average score of 22.5 and the third cycle achieve both criteria with an average score of 27. While the average value of the end of individual students increases every cycle. In the first cycle of 56.44, the second cycle of 72.22, and the third cycle of 84.79. Ccompleteness of classical study in the first cycle of 27.02%, cycle II reached 67.57% and 91.89% for the third cycle that has been achieved based on the criteria established in advance is at least 80%.